Investigating the critical issues in the conservation of heritage building: The case of China. (1st July 2022) - Shan, Ming; Chen, Yu-Fei; Zhai, Zhao; Du, Juan
Abstract: The importance of conserving heritage buildings is widely acknowledged, and considerable research studies have been conducted in this area. The extant literature mainly investigates the topic from the aspect of technology. This study aims to examine the management issues in the conservation of heritage buildings. To achieve this goal, pilot interviews were conducted with experienced industry experts from China first, followed by a questionnaire administered to 58 practitioners working in the country's heritage building conservation sector. Non-parametric statistical methods were used to analyze the collected data. Results revealed that "extreme vulnerability to fire hazard, " "loss of traditional craftmanship, " "adverse impact from weather, " "increased material cost due to the small size of the project, " and "outdated budget quota" were the top five critical issues to the conservation of heritage buildings in China. Recommendations that may help address these issues were also provided at the end of this paper. This study enriches the knowledge by exploring the critical issues affecting the conservation of heritage buildings. Additionally, the findings from this study are useful to the industry practitioners, as they can help the industry formulate effective measures to tackle these critical issues. Highlights: 17 management issues in current conservation of heritage buildings in China are identified. Top five critical issues affecting heritage building conservation in China are analyzed. Solutions that may address these issues are provided.